Agricultural development in a changing world - Fan, Shenggen; Otsuka, Keijiro (International Food Policy Research Institute, 2021)
The world has been changing rapidly, and major issues surrounding agriculture have evolved as well. In fact, over the last several decades major shifts have occurred in the thinking on and practice of agricultural development. Accordingly, agricultural development goals have moved far beyond traditional ones such as food production and availability, agricultural productivity, farmers’ incomes (particularly those of smallholders), and employment. The set of new goals includes poverty reduction, adequate nutrition, functioning food value chains (FVCs), environmental sustainability, climate adaptation and mitigation, and gender equality and equity. Looking forward, agriculture will face new challenges and will have to be positioned to deliver broader development outcomes such as those mandated under the Sustainable Development Goals (SDGs).